2022
DOI: 10.22201/fmvz.24486760e.2022.1088
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors, and main characteristics of bruises in cattle: A meta-analysis in the American continent

Abstract: Bruises threaten the welfare of cattle because they cause pain, suffering, and stress during the pre-slaughter stage. Thus, we used meta-analyses to estimate the prevalence of carcass bruising in cattle from the American continent, determined the characteristics of the bruises, and calculated the odds ratio (OR) of risk factor categories associated with bruising. We searched electronic databases to retrieve primary studies conducted in the American continent, which reported cattle carcass bruising, analyzed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Sex was an animal-related characteristic associated with carcass bruising, i.e., heifers had less bruising than steers. Other studies have identified sex as a risk factor for bruising ( Mendonça et al., 2018 ; Sánchez et al., 2022 ), although the findings are highly variable, and the reasons for this are unclear. Behavioral differences between different sex classes may explain the variation in bruise prevalence ( Kline et al., 2020 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Sex was an animal-related characteristic associated with carcass bruising, i.e., heifers had less bruising than steers. Other studies have identified sex as a risk factor for bruising ( Mendonça et al., 2018 ; Sánchez et al., 2022 ), although the findings are highly variable, and the reasons for this are unclear. Behavioral differences between different sex classes may explain the variation in bruise prevalence ( Kline et al., 2020 ).…”
Section: Discussionmentioning
confidence: 96%
“…This loss is attributed to overall reductions in carcass yield due to trimming, the devaluing of cuts affected by bruising, and the increased labor needed to trim bruises ( McNally and Warriss, 1996 ). Therefore, substantial work has been done to understand the risk factors associated with bruising to reduce its prevalence ( Kline et al., 2020 ; Sánchez et al., 2022 ; Zanardi et al., 2022 ). In the current study, the risk of carcass bruising was positively associated with lairage duration and is consistent with other work that found that bruising worsens with longer durations of lairage ( Warriss, 1990 ; Hoffman and Lühl, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate potential causes of heterogeneity, we conducted a meta-regression analysis using a random-effects D-L model [24]. We created separate univariate models with continuous moderators (study-level covariates) including sample size (calculated as quintiles for each species), year of publication, latitude of study location, and number of diagnostic techniques used.…”
Section: Summary Of Evidence and Statistical Analysis Of Datamentioning
confidence: 99%